The effect of nimodipine and prednisolone on traumatic facial nerve injury treatment - Dolen, Tolga; Kaygusuz, Irfan; Akpolat, Nusret; Alpay, Hayrettin Cengiz; Keles, Erol; Karlidag, Turgut; Yuksel, Koray (Deomed Publ, Istanbul, 2017)
Objective: To investigate the histopathological effect of nimodipine and prednisolone treatment on an animal model with peripheral facial nerve paralysis generated by clamping. Methods: Twenty-eight New Zealand originated rabbits with facial nerve paralysis of the buccal branches generated by clamping were divided into four groups of seven each, administered with nimodipine, methylprednisolone and nimodipine-methylprednisolone combination throughout 21 days. The injured neural tissues were investigated histopathologically after treatment regarding perineural fibrosis, collagen degeneration, axonal degeneration, myelin degeneration, Schwann cell proliferation, normal myelin structure, and edema. The groups were compared with each other and with the control group. Results: Statistically significant difference was determined between nimodipine and control groups regarding increased number of collagen fibers, myelin degeneration, axonal degeneration and myelin structure; between nimodipine and methylprednisolone groups, and between nimodipine and nimodipine-methylprednisolone combination groups regarding edema (p< 0.05). Statistically significant data were also found between methylprednisolone and control groups in terms of increased number of collagen fibers, myelin degeneration, axonal degeneration and edema; between nimodipine-methylprednisolone combination and the control groups in terms of increased number of collagen fibers, myelin degeneration, axonal degeneration, normal myelin structure and edema (p< 0.05). Conclusion: Nimodipine and methylprednisolone both have positive effects on traumatic peripheral nerve paralysis with nerve integrity preserved whereas advantage of nimodipine over methylprednisolone cannot be suggested.
Keywords: Facial nerve paralysis; nimodipine; methylprednisolone